2021
DOI: 10.3390/ijms22105292
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of RNA-Binding Proteins and microRNAs in Neurodegenerative Diseases

Abstract: The number of patients with neurodegenerative diseases (NDs) is increasing, along with the growing number of older adults. This escalation threatens to create a medical and social crisis. NDs include a large spectrum of heterogeneous and multifactorial pathologies, such as amyotrophic lateral sclerosis, frontotemporal dementia, Alzheimer’s disease, Parkinson’s disease, Huntington’s disease and multiple system atrophy, and the formation of inclusion bodies resulting from protein misfolding and aggregation is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 235 publications
(327 reference statements)
0
29
0
Order By: Relevance
“…Among the most significant advances in human neuroscience, neurology and molecular neurogenetics over the last fifteen years are: (i) the discovery of a family of small noncoding single-stranded RNAs called microRNAs in the mammalian brain and cen-tral nervous system (CNS) and (ii) the analysis and categorization of their abundance, speciation and complexity in development, aging and in neurological health and CNS disease [2,5,6,9,70,71,93,101,107]. A growing body of evidence indicates that select species of the 2650 member human miRNA gene family are brain-abundant and participate in the initiation, propagation and development of insidious age-related neurological disorders of the mammalian brain and CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most significant advances in human neuroscience, neurology and molecular neurogenetics over the last fifteen years are: (i) the discovery of a family of small noncoding single-stranded RNAs called microRNAs in the mammalian brain and cen-tral nervous system (CNS) and (ii) the analysis and categorization of their abundance, speciation and complexity in development, aging and in neurological health and CNS disease [2,5,6,9,70,71,93,101,107]. A growing body of evidence indicates that select species of the 2650 member human miRNA gene family are brain-abundant and participate in the initiation, propagation and development of insidious age-related neurological disorders of the mammalian brain and CNS.…”
Section: Discussionmentioning
confidence: 99%
“…However, genome-wide analysis of all known human miRNAs, with a current total of~2650 individual species, indicates that the RNA sequence of human miRNAs has been highly selected from many different RNA sequence possibilities. Interestingly, some miRNAs have been shown to maintain their exact or highly homologous miRNA ribonucleotide sequence between plants and animals over~1.5 billion years of evolution (the Arabidopsis thaliana-Homo sapiens divergence), indicating that highly conserved ribonucleotide sequence-mediated genetic regulatory functions are attributable to the same miRNAs and miRNA binding proteins over vast periods of time [1,8,9]. Further RNA-sequencing and array-based analyses have indicated that only certain miRNAs, probably about 25-30 individual miRNA species: (i) are abundant in the cytoplasm of the human brain as well as retinal and other CNS cells; (ii) are inducible by pathological factors, such as pro-inflammatory cytokines and chemokines; and (iii) are upregulated by different types of pathogenic microbes, including viral gene-encoded products and highly neurotoxic secreted bacterial exudates such as lipopolysaccharide (LPS) [5,10,11] see below.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Aberrant RNA–RNA interactions leading to the sequestration and/or dysregulation of RNA-binding proteins in MLOs may be one of the major driving forces behind neurodegenerative diseases [ 11 , 542 , 947 , 948 , 949 ]. Aberrant LLPS as a result of deficient RNA-binding in TDP-43 can form pathogenic, insoluble aggregates that are excluded from physiological SGs.…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%
“…Aberrant RNA–RNA interactions leading to the sequestration and/or dysregulation of RNA-binding proteins in MLOs may be one of the major driving forces behind neurodegenerative diseases [ 11 , 542 , 947 , 948 , 949 ]. Section 5.5 discussed the formation of SGs in response to various stress conditions involving the sequestration of translationally stalled mRNA and RNA-binding proteins [ 541 , 542 , 912 , 913 ], where the mechanism of selection for mRNA inclusion in SGs is determined by oxidative stress-dependent m 6 A mRNA modifications by “reader” YTHDF3 [ 950 , 951 ].…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%
“…It is therefore important to adequately understand their functioning, which could lead to the discovery and development of novel drug candidates [ 14 ]. RBPs have been linked to diseases such as Alzheimer’s and Parkinson’s disease [ 15 ], autism spectrum [ 16 ], schizophrenia [ 17 ], and other central nervous system (CNS) disorders. Specifically, the RBPs expressed in the CNS are mainly involved in alternative splicing, the process that allows the obtainment of different isoforms of a protein, starting from a single gene.…”
Section: Introductionmentioning
confidence: 99%